Analysis of Pyramidal Surface Texturization of Silicon Solar Cells by Molecular Dynamics Simulations. (21st October 2008) - Chung, Hsiao-Yen; Chen, Chiun-Hsun; Chu, Hsin-Sen
Abstract : The purpose of this paper is to explore the relations between surface texturization and absorptance of multicrystalline silicon solar cells by a simple new model, based on the classic molecular (MD) dynamics simulation, alternative to complex electron-photon interactions to analyze the surface texturization of solar cells. In this study, the large tilted angle leads to the lower efficiency of solar cell. To consider the effect of incident angle, a range of high efficiency exists due to the increasing probability of second reflection. Furthermore, the azimuth angle of incident light also affects the efficiency of solar cells. Our results agree well with previous studies. This MD model can potentially be used to predict the efficiency promotion in any optical reflection-absorption cases.